A case of auricular tuberculosis - Is it congenital or neonatal tuberculosis? - Kumar, R. Kishore; Yerur, Kishore Vrajananda (Indian Journal of Child Health, 2018)
Tuberculosis (TB) in children is one of the leading infectious diseases worldwide and is still a serious public health problem in many countries. True congenital TB is rare; the greatest threat to the neonate is the acquisition of TB infection shortly before or after birth, which tends to progress rapidly to serious TB disease in a large proportion of untreated infants. The definition of congenital TB is so stringent that some cases of neonatal TB like the one we are reporting here lead to confusion as to whether we should report it as congenital TB or neonatal TB. We report an unusual case of localized auricular TB in a preterm neonate. Neonatal TB is rare but can be severe.